2021
DOI: 10.1136/medethics-2021-107275
|View full text |Cite
|
Sign up to set email alerts
|

Patients, clinicians and open notes: information blocking as a case of epistemic injustice

Abstract: In many countries, including patients are legally entitled to request copies of their clinical notes. However, this process remains time-consuming and burdensome, and it remains unclear how much of the medical record must be made available. Online access to notes offers a way to overcome these challenges and in around 10 countries worldwide, via secure web-based portals, many patients are now able to read at least some of the narrative reports written by clinicians (‘open notes’). However, even in countries th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 66 publications
(119 reference statements)
1
43
0
Order By: Relevance
“…These concerns seem to be comprehensible from a professional point of view; however, instead of denying access to a subset of patients or not informing them about the possibility of accessing their EHR, one of the included studies recommended offering an educational program on the use of PAEHR to learn about the benefits and misuses of reading therapy notes, and to discuss possible adverse side effects with each individual SU. Discussion about restricting access to the EHR to only a subset of SUs, however, can be considered contrary to the basic idea of coproduction and may lead to epistemic injustice [73]. This might also apply to partial access restrictions, such as sharing notes only on a case-by-case basis or the release of clinical notes after an acute mental crisis has subsided [31].…”
Section: Special Challenges In Mhcmentioning
confidence: 99%
“…These concerns seem to be comprehensible from a professional point of view; however, instead of denying access to a subset of patients or not informing them about the possibility of accessing their EHR, one of the included studies recommended offering an educational program on the use of PAEHR to learn about the benefits and misuses of reading therapy notes, and to discuss possible adverse side effects with each individual SU. Discussion about restricting access to the EHR to only a subset of SUs, however, can be considered contrary to the basic idea of coproduction and may lead to epistemic injustice [73]. This might also apply to partial access restrictions, such as sharing notes only on a case-by-case basis or the release of clinical notes after an acute mental crisis has subsided [31].…”
Section: Special Challenges In Mhcmentioning
confidence: 99%
“…A study based on Miranda Fricker's concept of 'epistemic injustice' emphasizes, among other things, denying patients access to their medical records may lead to ethical wrongs [1]. According to Fricker, the sharing and production of knowledge is a valued good; as such, inequalities in access to such knowledge and to participation in knowledge formation activities constitute an ethical wrong that can lead to primary and secondary harms [33].…”
Section: Discussionmentioning
confidence: 99%
“…Failure to access notes also means that patients cannot correct errors, omissions, or inaccuracies in their records. Blease et al [1] argue that there is growing evidence that people with psychiatric illnesses may be more vulnerable to this type of injustice, as they are often seen negatively as unable to understand or cope with the information in their clinical notes. Should epistemic injustice indeed be an accurate portrayal of what happens when patients are denied access to their psychiatric notes, this study finds evidence of systematic structural barriers to access in Sweden.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 In a recent extension of this trend, the 21st Century Cures Act also mandates provision of straightforward and open access to clinician notes. 10 Early studies have suggested that oncology patients have interest in and may benefit from this practice. 11 While considering the potential benefits of data exchange, however, we must remember that the order of information delivery clearly matters.…”
mentioning
confidence: 99%